Penerapan Metode Group Resume melalui Media Film Dokumenter untuk Meningkatkan Aktivitas dan Hasil Belajar Sejarah Siswa Kelas XI SMAN 1 Rantau Kobar - Gustina Gustina (Departement of Mathematics Education, 2022)
This study aims to obtain information and discuss the application of the group resume method through documentary film media to increase the activity and results of studying history for class XI students of SMAN 1 Rantau Kobar. This research is a classroom action research which consists of two cycles. Each cycle has four stages, namely planning, implementing, observing, and reflecting. This research was conducted at SMAN 1 Rantau Kobar with class XI students as subjects. Data collection techniques using observation sheets, tests, field notes and documentation. Data were analyzed using percentages and data reduction. Based on the results of the research and discussion, it can be concluded that the application of the group resume method through documentary film media can increase the activity and results of learning history for class XI students of SMAN 1 Rantau Kobar.